2020
DOI: 10.1093/heapol/czaa156
|View full text |Cite
|
Sign up to set email alerts
|

How to reduce household costs for people with tuberculosis: a longitudinal costing survey in Nepal

Abstract: The aim of this study was to compare costs and socio-economic impact of tuberculosis (TB) for patients diagnosed through active (ACF) and passive case finding (PCF) in Nepal. A longitudinal costing survey was conducted in four districts of Nepal from April 2018 to October 2019. Costs were collected using the WHO TB Patient Costs Survey at three time points: intensive phase of treatment, continuation phase of treatment and at treatment completion. Direct and indirect costs and socio-economic impact (poverty hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 26 publications
4
25
0
Order By: Relevance
“…The coping strategies like borrowing money, selling assets, and mortgaging household assets were also reported to be employed by patients with TB in India, Myanmar, Soloman Islands, Nepal, Malawi, Tajikistan, Benin, Ghana, China, South Africa, Bangladesh, and Tanzania. 5,[7][8][9][10][11][12][13][14][15][16][17][18] Our findings are also similar to the coping strategies described among patients with TB-diabetes comorbidity 19 , and TB-HIV co-infection. 20 Our study findings on enabling factors were supported by several other studies.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The coping strategies like borrowing money, selling assets, and mortgaging household assets were also reported to be employed by patients with TB in India, Myanmar, Soloman Islands, Nepal, Malawi, Tajikistan, Benin, Ghana, China, South Africa, Bangladesh, and Tanzania. 5,[7][8][9][10][11][12][13][14][15][16][17][18] Our findings are also similar to the coping strategies described among patients with TB-diabetes comorbidity 19 , and TB-HIV co-infection. 20 Our study findings on enabling factors were supported by several other studies.…”
Section: Discussionsupporting
confidence: 78%
“…Studies have reported various negative financial coping strategies such as borrowing money, selling assets such as jewellery, interrupting school, and others. 3,5,[7][8][9][10][11][12][13][14][15][16][17][18] Such financial coping strategies are even considered a proxy indicator of catastrophic costs employed by patients with TB. 17 Further, dissaving serves as an indicator of the financial protection mechanisms employed by governments to help them balance such costs.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these epidemiologic benefits, the NTP has placed a strong emphasis on ACF in the recent past [14][15][16][17]. However, to date the evidence on the socio-protective nature of ACF remains limited [18,19] with none available for the Vietnamese context.…”
mentioning
confidence: 99%
“…Nevertheless, it is important to conduct such camps as the study screened and tested a large number of people who are not able to access diagnosis in other ways. Such strategies improve equity of access to quality TB services, reduce patient incurred costs from TB illness in the most impoverished population groups, and are essential to “leave no-one behind” in countries with large remote rural populations [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%